2008
DOI: 10.1007/s00432-008-0375-5
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal honokiol, a promising agent for treatment of cisplatin-resistant human ovarian cancer

Abstract: The present findings suggest that Lipo-HNK may provide an effective approach to inhibit tumor growth in both cisplatin sensitive and -resistant human ovarian cancer with minimal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…Recently, magnolol and honokiol have been reported to have antitumor action by inhibiting proliferation, inducing apoptosis and differentiation, countering metastasis, suppressing angiogenesis, and reversing multidrug resistance (10,28,29). Numerous signaling pathways have been implicated in the regulation of apoptosis by magnolol and honokiol (30).…”
Section: Magnolol and Honokiolmentioning
confidence: 99%
“…Recently, magnolol and honokiol have been reported to have antitumor action by inhibiting proliferation, inducing apoptosis and differentiation, countering metastasis, suppressing angiogenesis, and reversing multidrug resistance (10,28,29). Numerous signaling pathways have been implicated in the regulation of apoptosis by magnolol and honokiol (30).…”
Section: Magnolol and Honokiolmentioning
confidence: 99%
“…Previous reports demonstrated that honokiol could treat cancers by causing cell cycle arrest (6,7), inhibiting angiogenesis (8), and inducing apoptosis (9)(10)(11)(12). Meanwhile, honokiol could overcome conventional drug resistance (13)(14)(15) and also showed synergistic antitumor effect with other anticancer agents such as cisplatin or adriamycin (16,17). When many studies around the pharmacodynamics and pharmacology of honokiol attract great attention, questions around the formulation of honokiol should also be attended due to the fact that honokiol is water insoluble.…”
Section: Introductionmentioning
confidence: 97%
“…In brief, the cells (1 × 10 4 in 100 μL) were seeded on 96-well plates in triplicate. Following a culture at 37 for 24 ℃ h, the medium was replaced with fresh medium at various concentrations of HNK (10,15 Co., USA) [14].…”
Section: -(45-dimethylthiazol-2-yl)-25-diphenyltetrazolium Bromidementioning
confidence: 99%
“…Following a 24h-culture at 37 , the media were repla ℃ -ced with fresh medium at various concentrations of HNK (10,15 [15].…”
Section: Propidium Iodide Assaymentioning
confidence: 99%
See 1 more Smart Citation